Pengaruh pH Dan Waktu Kontak Ozonisasi Terhadap Biodegradability Limbah Cair Tahu Dan Kotoran Sapi - Khalidazia Putri; David Andrio; Elvi Yenie (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Tofu wastewater has COD and BOD concentration of 3,305 and 1,250 mg/L respectively and the volume of waste by 14-20 L/kg of soybeans were process. The low of COD content causes the anaerobic digestion process not optimal to produce methane gas, that needs to be added the other of organic matter such as cow dung. However, lignin and organic polymer in a cow dung causes the mixed of tofu wastewater and cow dung difficult to biodegradable. To improve the biodegradability could be performed by pre-treatment with ozonation process. The aims of this study to determined the effect of pH range (5.22; 8 and 10) and the time of ozonation contact (20; 40 and 60 minutes) to the COD value. The results showed an increase in the percentage of removal COD. The optimum condition was shown at pH 10 time of ozonation was 60 minutes where the percentage of removal COD was 54,8%. The conclusion of this study the higher pH and the longer time of ozonation showed the better of removal the COD.Kata Kunci : Advanced Oxidation Procces, ozonation, biodegradability, BOD5/COD ratio.